Building Inclusive Community by Bridging Worldview Differences: A Call to Action From the Interfaith Diversity Experiences and Attitudes Longitudinal Survey (IDEALS). Issue 3 (3rd July 2017) - Rockenbach, Alyssa N.
Abstract: Adapted from a keynote address delivered at the 2017 Dalton Institute on College Student Values, this article introduces findings from the Interfaith Diversity Experiences and Attitudes Longitudinal Survey (IDEALS), a national study aimed at identifying the high-impact practices most conducive to students' interfaith learning and engagement. Informed by data collected from more than 20, 000 first-year students attending 122 diverse colleges and universities, the article addresses how higher education leaders can build community, cooperation, and trust on campus in an era of intensified religious, ideological, and political conflict.